Multi-angle aerosol optical depth retrieval method based on improved surface reflectance - L. Chen; R. Wang; Y. Fei; P. Fang; Y. Zha; H. Chen (Atmospheric Measurement Techniques, 2024)
Retrieval of atmospheric aerosol optical depth (AOD) has been a challenge for Earth satellite observations, mainly due to the difficulty of estimating surface reflectance with the combined influence of land–atmosphere coupling. Current major satellite AOD retrieval products have low spatial resolution under complex surface processes. In this study, we further improved the surface reflectance by modeling the error correction based on the previous AOD retrieval and obtained more accurate AOD retrieval results. A lookup table was constructed using the Second Simulation of Satellite Signal in the Solar Spectrum (6S) to enable high-precision AOD retrieval. The accuracy of the algorithm's retrieval was verified by observations of the Aerosol Robotic Network (AERONET). From the validation results, we find that among the nine Multi-angle Imaging SpectroRadiometer (MISR) angles, the retrieved AOD has the best retrieved results with the AOD observed at the An angle (Taihu: R = 0.81, relative mean bias (RMB) = 0.68; Xuzhou-CUMT: R = 0.73, RMB = 0.78). This study will help to further improve the retrieval accuracy of multi-angle AOD at large spatial scales and long time series. The retrieved AOD based on the improved method has the advantages of fewer missing pixels and finer spatial resolution compared to the MODIS AOD products and our previous estimates.